Starting a Community Garden - Adrian Hunsberger; Eva C. Worden; John McLaughlin (EDIS)
A community garden is a great way to unite a group of people in a common goal. In addition to providing fresh herbs, vegetables, and fruit, community gardens can also increase self-esteem, beautify a neighborhood, and create an opportunity for socializing and improving health. This revised 4-page fact sheet outlines the importance of community gardens and how to develop and manage a community garden. Written by Adrian Hunsberger, Eva C. Worden, and John McLaughlin, and published by the Environmental Horticulture Department, April 2016.